The Effects of Macroeconomic Shocks on Trends of Region's Foreign Economic Activity - Yuri I. TRESHCHEVSKY; Anna Yu. KOSOBUTSKAYA; Elena A. OPOIKOVA; Olga N. PAPINA (Communications of International Proceedings, 2020)
The goal of the research is to identify long-term trends in the foreign economic activity in the Russian region with a medium level of development and to evaluate the effects of macroeconomic shocks on them. Methods of research. The research has been carried out using the following techniques. Cluster analysis is used to identify homogeneous groups of regions with similar parameters of different types of foreign economic activity. Comparative analysis to establish model regions reflecting characteristics of the respective clusters development. Correlation and regression analysis to investigate the dynamics of different types of foreign economic activity and logical analysis to establish the nature of impact of macroeconomic shocks on the parameters of foreign economic activity. Results. The study identified the features of development of different types of foreign economic activities in the "medium” region of Russia. It has been estimated that the impacts of macroeconomic shocks on exports to the CIS and non-CIS countries, on imports from both groups of countries, on technologies and technical services exchange and on foreign investments are of different nature.
Keywords: Region; Foreign Economic Relations; Macroeconomic Shocks.